Spatial disparity and associated factors of diarrhea among under-five children in Rwanda: a multilevel logistic regression analysis - Abiyu Abadi Tareke; Sebwedin Surur Jemal; Getahun Dejene Yemane; Hamdi Fekredin Zakaria; Enyew Woretaw Shiferaw; Anaclet Ngabonzima (BMC, 2024)
Abstract Background Diarrhea, defined as three or more loose stool per day, is a major cause of child mortality. Exploring its spatial distribution, prevalence, and influencing factors is crucial for public health decision and targeted interventions. This study aimed to investigate these aspects using 2019 Rwanda demographic health survey data. Method A total 7,978 (weighted) under-five children were included in this study. Spatial clustering (hotspots areas) were mapped using ArcGIS and SaTscan software. A multilevel logistic regression model was fitted to assessed factors associated with diarrhea, reporting significance at p < 0.05 and a 95% confidence interval. Results diarrheal diseases in Rwanda showed a clustered spatial pattern (Moran's I = 0.126, p = 0.001), with the primary cluster in west and north provinces. Under-five diarrhea prevalence was 14.3% (95% CI: 13.55, 15.08). Factors increasing likelihood included maternal age 15-34 years, child age 7-24 months, while full immunization was protective (aOR = 0.74, 95% CI: 0.56, 0.98). Conclusion Spatial clustering of diarrheal diseases is found in west and north provinces of Rwanda. Being born to a young mother, being a child aged 7-24 months, being fully immunized, being born to a low-educated mother and belonging to a community having low level education are factors associated with diarrheal diseases in Rwanda. Developing interventional plans based on identified clusters and approaching children based on their immunization status, maternal education and age could be cost-effective in reducing diarrheal diseases in Rwanda. Location based intervention could allow for the efficient allocation of resources by focusing on areas with higher prevalence and need.